EXPERIMENTAL AIR-SHIPMENT OF CARP FRY IN PLASTIC BAGS - Ranade, M R; Kevalramani, H G (Indian Journal of Fisheries, 2015)
With the object of intensifying carp culture in the Bombay State the Department of Fisheries, Bombay, imported this year (1955) from Calcutta 11 lakhs of carp fry, as against not more than 4 lakhs in any of the previous years. The fry consisted mostly of Labeo rohita (Ham.), Catla catla (Cuv. and Val.) and Cirrhina mrigala (Ham.). As usual, these were brought by rail in earthen pots or hundies. Approximately 1,200 fry, measuring not more than 1" in size, were contained in each hundie